The effect of interval training on the development of strength and accuracy of the two legs Basketball scoring (Journal of the College of Basic Education, 2022)
The strength is characterized by speed and accuracy of scoring, and the research problem lies in the lack of interest in the endurance side, as it did not take its real role and size in the training process within the curricula prepared by the trainers and their various methods and according to the correct scientific method, so the researchers decided to study this problem, and the research aims to prepare a training program To develop the strength, speed and accuracy of scoring among youth basketball players.The researchers used the experimental method by comparing the experimental group with the control group